1988
DOI: 10.1111/j.1360-0443.1988.tb00506.x
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis and Cognitive Functions: a re‐evaluation study

Abstract: Out of 25 each of long-term, heavy bhang (marihuana) ingestors, 25 charas (hashish) smokers and 25matched non-user controls earlier studied and reported by us, 11 bhang users, 19 charas smokers and 15 controls could be re-studied after a lapse of 9-10 years. All the users had continued the use during the intervening years. Tests of intelligence, memory and perceptuo-motor tasks earlier administered to the subjects were repeated. This showed a significant additional deterioration in case of the users on a numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 6 publications
1
15
0
1
Order By: Relevance
“…Schneier and Siris (1987) propose that there is a clear association between the emergence of psychotic symptoms and personality alterations in cannabis abusers. Mendhiratta et al (1988) reported that neuroticism as evaluated through the Minnesota Multiphasic Personality Inventory test is more intense in subjects with toxic psychosis, and Negrete (1983) reported similar results.…”
Section: Epidemiological Studiessupporting
confidence: 53%
“…Schneier and Siris (1987) propose that there is a clear association between the emergence of psychotic symptoms and personality alterations in cannabis abusers. Mendhiratta et al (1988) reported that neuroticism as evaluated through the Minnesota Multiphasic Personality Inventory test is more intense in subjects with toxic psychosis, and Negrete (1983) reported similar results.…”
Section: Epidemiological Studiessupporting
confidence: 53%
“…Foremost among the findings from longitudinal studies such as the Dunedin study are that executive functioning ( Meier et al, 2012 ) and processing speed or reaction time ( Mendhiratta et al, 1988 ; Wilson et al, 1994 ; Hunault et al, 2009 ) tend to be the most susceptible to the long-term marijuana use and that disruptions of these neurocognitive processes can eventually lead to motivational and academic difficulties (for reviews, see Lynskey and Hall, 2000 ; Gruber and Pope, 2002 ; Volkow et al, 2014 ). These findings have also been bolstered by the human studies examining the acute and chronic effects of Δ 9 -THC, which have documented Δ 9 -THC-induced disruptions in a number of domains of neuropsychological functioning.…”
Section: Introductionmentioning
confidence: 99%
“…Pope et al (2002) found similar memory impairments up to 7 days after marijuana use ceased, but were unable to find a significant difference between users and controls after 28 days of abstinence. Other studies provide mixed evidence regarding residual neuropsychological deficits resulting from marijuana use (Mendhiratta et al 1988;Schwartz et al 1989 ;Solowij et al 1991 ;Lyketsos et al 1999 ;Varma et al 2000). Where differences between users and non-users have been found, they are often on only one or two tests out of a large number administered ; moreover, the differences are often modest, and users' scores are usually within the range of normal cognitive variability (Block & Ghoneim, 1993).…”
Section: Introductionmentioning
confidence: 99%